Psychosocial work environment and teachers\ psychological well-being: the moderating role of job control and social support - Afrizal, Teuku (Tanjung Malim, 2021)
Psychosocial work environment and teachers\ psychological well-being: the moderating role of job control and social support by Afrizal, Teuku